2017
DOI: 10.1371/journal.pone.0170193
|View full text |Cite
|
Sign up to set email alerts
|

A Common Variant in SCN5A and the Risk of Ventricular Fibrillation Caused by First ST-Segment Elevation Myocardial Infarction

Abstract: BackgroundSeveral common genetic variants have been associated with either ventricular fibrillation (VF) or sudden cardiac death (SCD). However, replication efforts have been limited. Therefore, we aimed to analyze whether such variants may contribute to VF caused by first ST-elevation myocardial infarction (STEMI).MethodsWe analyzed 27 single nucleotide polymorphisms (SNP) previously associated with SCD/VF in other cohorts, and examined whether these SNPs were associated with VF caused by first STEMI in the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 38 publications
2
21
0
1
Order By: Relevance
“…Our results are in agreement with a case-control study that found no association between 24 common genetic variants, including rs2200733, related to AF and the risk of VF in the setting of first STEMI. 40 Our results support the idea that cardiac electrical abnormalities may be the result of variations in genes coding ion channels. On the other hand, our study shows that SNPs in genes involved in embryonic cardiogenesis, previously associated with congenital heart rhythm diseases, are not associated with acquired heart rhythm disorders.…”
Section: Discussionsupporting
confidence: 85%
“…Our results are in agreement with a case-control study that found no association between 24 common genetic variants, including rs2200733, related to AF and the risk of VF in the setting of first STEMI. 40 Our results support the idea that cardiac electrical abnormalities may be the result of variations in genes coding ion channels. On the other hand, our study shows that SNPs in genes involved in embryonic cardiogenesis, previously associated with congenital heart rhythm diseases, are not associated with acquired heart rhythm disorders.…”
Section: Discussionsupporting
confidence: 85%
“…One SNP located in intron 1 of SCN5A (rs11720524) showed an association with arrhythmic risk. 64 However, when the field moved from candidate genes to GWAS, none of the SNPs or the genes previously associated with lifethreatening arrhythmias in different clinical settings and during AMI showed a significant signal. Two GWAS reported an association of common genetic variants with VF/SCD at a genome-wide statistical significance (P < 5 Â 10 -8 ).…”
Section: Acute Myocardial Infarctionmentioning
confidence: 99%
“…В первой части исследования были изучены полиморфизмы трех генов GNB3, GNAQ, GNAS в отношении ассоциа-лено, что ассоциация полиморфизма с ВСС более выражена в группе больных с ИБС [15]. Известно, что полиморфизм rs11720524 гена ассоциирован с фибрилляцией желудочков [16]. Ген SCN5A (sodium voltage-gated channel alpha subunit 5, 3p22.2) кодирует α-субъединицу натриевого канала.…”
Section: Sri Of Therapy and Prevention Medicine -Branch Of Fsbsi Fedeunclassified